STRATEGI KOMUNIKASI ORANG TUA PADA ANAK BERKEBUTUHAN KHUSUS (ABK)(Analisa Teori Uncertanty Reduction Theory tentang Pengurangan Ketidakpastian) - Syahrudin; Khairunesa Isa (Fakultas Dakwah Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2023)
Abstract This discussion aims to describe how people communicate in an effort to reduce suffering in children with special needs. The theory used is the Uncertainty Reduction Theory. The results of the analysis in this study indicate that the experience of delivering communication experienced by parents occurs when they have to convey a message, such as when teaching something or giving an understanding of a condition because children tend to be slow to process and do not care about the condition of their parents. In addition, increases increase because parents cannot know exactly what their child is thinking. Parents with children with mild special needs tend to treat children the same as other children because only intellectual differences are visible, while parents with children with moderate special needs can place themselves more. Even so, parents still accept whatever the child's condition is and hope that the child can develop in a better direction. Emotional closeness and inherent self-image also play a role in reducing freedom of communication. Parents who are closer and open to their children have warmer and more intimate relationships than those who do not. Therefore, parents who are aware of this make the feeling of uncertainty that arises when interacting can be managed properly and effective communication is established because children do reciprocity. Thus, parents can better understand children with special needs.